Fuzzy Logic Implementation In Internet Of Things Technology For Foging Greenhouse Plants - Suyud Widiono; Iwan Hartadi TU (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Misting of plants in a greenhouse has an important role in maintaining the environmental humidity that plants need. Obstacles faced to maintain the humidity of the plant environment is the use of a thermometer as a measuring tool and misting is still manual. Based on these problems, this research presents an automatic misting system for plants in a greenhouse using the fuzzy logic method. The process of taking data on the temperature and humidity of the plant environment in the greenhouse is from the DHT11 sensor value which is read by the microcontroller to be stored in the Firebase cloud database, the temperature and humidity data in the cloud database is sent and displayed in real-time by an android application built with the MIT tool App Inventor 2. Apart from displaying temperature and humidity data from Firebase, the Android application also processes it using fuzzy logic to produce PWM (Pulse Width Modulation) values to set the fog time. The fuzzy logic method was chosen to map input data problems to output data in conducting fog control. From the sensor test, the results obtained from the comparison of DHT11 sensor readings have an average error of 2.73%. The duration of watering is carried out using Fuzzy logic, the total amount of watering in a day is 2,500 ml of water with a duration of 75 seconds, so that the fogging with the fuzzy logic method is in accordance with the conditions needed in the greenhouse room.